Environmental physiotherapy and the case for multispecies justice in planetary health. (18th November 2022) - Maric, Filip; Nicholls, David A.
ABSTRACT: Background: Global environmental change is fundamentally altering the composition and functioning of our planetary ecosystem. Effectively presenting the largest threat to the health of present and future generations, these changes and their health impacts are forcing us to think and practice healthcare in much broader terms than ever before. Objective: In this article, we provide an early outline for a radically otherwise, yet strangely familiar, environmental physiotherapy developed through a succession of carefully developed arguments. Discussion: We show how an underpinning belief in human exceptionalism has engendered an exploitative relationship with our natural planetary environment that has both shaped Western science and healthcare and led to our current environmental health crisis. Building on the dependence of human health on our planetary ecosystem, approaches like planetary health hold great promise for a corresponding, paradigmatic turn in healthcare. They fall short of this however, where they perpetuate anthropocentric interests and interventionist practices that have underpinned healthcare to date. Drawing on ethical and post-human philosophies we argue against human exceptionalism and for a solidarity that includes other-than-humans as the primary characteristic of planetary existence. Conclusion: Building on this foundation, we provide an early outline for a radically otherwise, yet strangely familiar, environmental physiotherapy, grounded in ecological awareness, multispecies justice, and a range of consonant practices of passivity and accompaniment, conceived as an alternative to the commonplace interventionism of healthcare.